Lack of N2-gene amplification on the Cepheid Xpert Xpress SARS-CoV-2 assay and potential novel causative mutations: A case series from Auckland, New Zealand. (2021) - Fox-Lewis, Shivani; Fox-Lewis, Andrew; Harrower, Jay; Chen, Richard; Wang, Jing; de Ligt, Joep; McAuliffe, Gary; Taylor, Susan; Smit, Erasmus
Abstract: We describe three cases with viral strains that demonstrate impaired N2-gene detection on the Cepheid Xpert Xpress SARS-CoV-2 assay, with two previously undescribed single nucleotide polymorphisms (SNPs): C29197T and G29227T. We propose that these SNPs are likely responsible since they are in close proximity to the previously described C29200T/C29200A SNPs, already shown to abolish N2-gene detection by the Xpert assay. Whether these SNPs abolish N2-gene detection by the Xpert assay individually or only in combination requires more work to elucidate.